RANCANG BANGUN APLIKASI PENDAFTARAN CALON PESERTA DIDIK BARU PADA SANGGAR TARI BUNGARAN - Iwan setiawan; Fajriyah Fajriyah (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
Bungaran Dance Studio is a place for teaching and learning activities about regional arts, especially Prabumulih regional arts. Sanggar Bungaran still registers manually in which prospective students must come to the activity site to register. Based on the results of this study, the researchers tried to design an android-based registration system to make it easier for prospective participants and the Bungaran Dance Studio to register. Application Design for New Student Candidates Registration At the Bungaran Dance Studio there are four database tables as well as seven form displays and nine interface displays that describe the system design in android form. The design of this application uses a spiral development method that is in accordance with the intended research object, and uses a design tool in the form of UML, and uses a database storage area in the form of MySQL. With this registration system, it is hoped that it can help prospective new students to register anywhere and anytime without having to come to the place where the activity takes place.